The clinical efficacy of melatonin in the treatment of patients with COVID-19: a systematic review and meta-analysis of randomized controlled trials - Huang, Po-Yu; Wu, Jheng-Yan; Liu, Ting-Hui; Tsai, Ya-Wen; Chen, Po-Tsang; Liao, Chia-Te; Toh, Han Siong (Frontiers in Medicine, 2023)
Background The COVID-19 pandemic has resulted in significant morbidity and mortality worldwide, with cytokine storm leading to exaggerating immune response, multi-organ dysfunction and death. Melatonin has been shown to have anti-inflammatory and immunomodulatory effects and its effect on COVID-19 clinical outcomes is controversial. This study aimed to conduct a meta-analysis to evaluate the impact of melatonin on COVID-19 patients. Methods PubMed, Embase, and Cochrane Central Register of Controlled Trials were searched without any language or publication year limitations from inception to 15 Nov 2022. Randomized controlled trials (RCTs) using melatonin as therapy in COVID-19 patients were included. The primary outcome was mortality, and the secondary outcomes included were the recovery rate of clinical symptoms, changes in the inflammatory markers like C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and neutrophil to lymphocyte ratio (NLR). A random-effects model was applied for meta-analyses, and further subgroup and sensitivity analyses were also conducted. Results A total of nine RCTs with 718 subjects were included. Five studies using melatonin with the primary outcome were analyzed, and the pooled results showed no significant difference in mortality between melatonin and control groups with high heterogeneity across studies identified (risk ratio [RR] 0.72, 95% confidence interval [CI] 0.47-1.11, p=0.14, I2=82%). However, subgroup analyses revealed statistically significant effects in patients aged under 55 years (RR 0.71, 95% CI 0.62-0.82, p<0.01) and in patients treated for more than 10 days (RR 0.07, 95%CI 0.01-0.53, p=0.01). The recovery rate of clinical symptoms and changes in CRP, ESR, and NLR were not statistically significant. No serious adverse effects were reported from melatonin use. Conclusion In conclusion, based on low certainty of evidence, the study concluded that melatonin therapy does not significantly reduce mortality in COVID-19 patients, but there are possible benefits in patients under 55 years or treated for more than 10 days. With a very low certainty of evidence, we found no significant difference in the recovery rate of COVID-19 related symptoms or inflammatory markers in current studies. Further studies with larger sample sizes are warranted to determine the possible efficacy of melatonin on COVID-19 patients.